INDUCTIVE APPROACH TO GRAMMAR TEACHING IN EFL CLASROOM - Orifjonova Durdona Muzaffar qizi; Qòchqorova Zulfizar Abduxamidovna (Лучшие интеллектуальные исследования, 2023)
Abstract: This research paper focuses on the important inductive approach to teaching a foreign language. The overall aim of this study is to provide learners with examples of the target grammatical structure and guide them to discover the rules and patterns through analysis and practice. This approach focuses on the principles of cognative learning theory and suggests that learners can easily remember grammar rules when they actively engage in the learning process.